Anti-social: An ethnographic account social media within a technically restrictive public sector agency - O’Connor, Ben (Journal of Interdisciplinary Studies in Education, 2019)
This article provides an ethnographic account of an action-research practitioner’s experience in social media usage within a public-sector agency that discourages and actively restricts social media usage on its ICT networks, and invokes policy against employee social media use. The agency is unique in the commercial, scientific and advisory services it provides, meaning that the sensitive nature of the work precludes the agency from being clearly identified – also a factor in its decision to restrict social media access. Nonetheless, events in similarly sized entities, such as the Royal Australian Navy, provide context for this study, and developments in other public sector agencies that offer similar services are provided to offer a frame of reference. Looking at the three main ways that employees are using social media at work, this examination discusses the implications for the future of collaborative work practices, and engagement with broader professional interests.